Antifungal Activity of Amphiphilic Perylene Bisimides (2022)
ABSTRACT: Perylene-based compounds, either naturally occurring or synthetic, have shown interesting biological activities. In this study, we report on the broad-spectrum antifungal properties of two lead amphiphilic perylene bisimides, compounds 4 and 5, which were synthesized from perylene-3,4,9,10-tetracarboxylic dianhydride by condensation with spermine and an ammonium salt formation. The antifungal activity was evaluated using a collection of fungal strains and clinical isolates from patients with onychomycosis or sporotrichosis. Both molecules displayed an interesting antifungal profile with MIC values in the range of 2-25 μM, being as active as several reference drugs, even more potent in some particular strains. The ammonium trifluoroacetate salt 5 showed the highest activity with a MIC value of 2.1 μM for all tested Candida spp., two Cryptococcus spp., two Fusarium spp., and one Neoscytalidium spp. strain. Therefore, these amphiphilic molecules with the perylene moiety and cationic ammonium side chains represent important structural features for the development of novel antifungals.